Experiences of teachers teaching grade 4 pupils with Mother Tongue-Based Multilingual Education (MTB-MLE): inputs to policy development and teacher training for MTB-MLE - Abrea, Adelyne Costelo; Ortua, Elvie Charie L.; Robles, Randy L. (Asia Pacific Higher Education Research Journal (APHERJ), 2020)
This phenomenological study described the experiences of 18 mathematics/science teachers of grade 4 pupils exposed to MTB-MLE from different divisions of Caraga using three modes of data gathering: survey questionnaire, classroom observation, and focus group discussion. Teachers perceived MTB-MLE as a barrier instead of being a bridge to learning concepts in English. However, they highlighted that MTB-MLE boosted the self-confidence of the pupils in expressing themselves using their Mother Tongue (MT). Teachers perceived the teaching of mathematics/science as challenging because of the pupils’ limited English vocabulary leading to problems in spelling, reading comprehension, and solving word problems. Translation is the most common strategy used by teachers to transition pupils from MT (L1) to English (L2). Training for teachers to effectively manage transition is suggested, as well as integration of MTB-MLE concepts to the Professional Education courses in teacher education institutions